Cultural Impact on Interactive Metadiscourse in Legal Hybrid Disciplines: A Comparative Genre Study: Comparative Genre Study - Al-Wazeer, Naseem; Ashuja’a, Abdulhameed (International Journal of Language and Literary Studies, 2025)
Cultural background can impact writers’ writing styles in academic contexts. The present study aimed to investigate this impact on research article (RA) abstracts in two legal hybrid disciplines (medical law and IT law) when used by native and non-native writers of English. By adopting corpus-based genre analysis, the present study explored the use of interactive metadiscourse markers (MMs) in 40 RA abstracts. The corpora were randomly chosen from two high-impact factor journals: "Health and Justice" (medical law) and "International Journal of Cyber Criminology" (IT law). For the analysis, Hyland’s (2005) interpersonal model of metadiscourse was applied. Other tools were also used: AntConc (2019) software, SPSS Version 27, and frequencies per 1000 words. The results revealed that there was a stronger presence of code glosses in the abstracts written by native writers compared to non-native writers. However, the differences between the native and non-native writers across the two disciplines were minimal and non-significant. This study suggests that both co-authorship with native writers and writing experience can reduce the influence of cultural background on non-native writers’ academic writing style.